Inhibition in Purified Systems and in Human Plasma of Chimaeric Plasminogen Activators Consisting of the NH2-Terminal Region of Tissue-Type Plasminogen Activator and the COOH-Terminal Region of UrokinaseType Plasminogen Activator - Lijnen, H R; Nelles, L; Van Hoef, B; De Cock, F; Collen, D (Thrombosis and Haemostasis, 1988)
Recombinant chimaeric molecules between tissue-type plasminogen activator (t-PA) and single chain urokinase-type plasminogen activator (scu-PA) or two chain urokinase-type plasminogen activator (tcu-PA) have intact enzymatic properties of scu-PA or tcu-PA towards natural and synthetic substrates (Nelles et al., J Biol Chem 1987; 262: 10855-10862). In the present study, we have compared the reactivity with inhibitors of both the single chain and two chain variants of recombinant u-PA and two recombinant chimaeric molecules between t-PA and scu-PA (t-PA/u-PA-s: amino acids 1-263 of t-PA and 144-411 of u-PA; t-PA/u-PA-e: amino acids 1-274 of t-PA and 138-411 of u-PA). Incubation with human plasma in the absence of a fibrin clot for 3 h at 37° C at equipotent concentrations (50% clot lysis in 2 h), resulted in significant fibrinogen breakdown (to about 40% of the normal value) for all two chain molecules, but not for their single chain counterparts. Preincubation of the plasminogen activators with plasma for 3 h at 37° C, resulted in complete inhibition of the fibrinolytic potency of the two chain molecules but did not alter the potency of the single chain molecules. Inhibition of the two chain molecules occurred with a t½ of approximately 45 min. The two chain variants were inhibited by the synthetic urokinase inhibitor Glu-Gly-Arg-CH2CCl with apparent second-order rate constants of 8,000-10,000 M−1s−1, by purified α2-antiplasmin with second-order rate constants of about 300 M−1s−1, and by plasminogen activator inhibitor-1 (PAI-1) with second-order rate constants of approximately 2 × 107 M−1s−1.It is concluded that the reactivity of single chain and two chain forms of t-PA/u-PA chimaers with inhibitors is very similar to that of the single and two chain forms of intact u-PA.
Keywords: Chimaeric plasminogen activators; Tissue-type plasminogen activator (t-PA); Urokinase-type plasminogen activator (u-PA)